Surface mapping of faceted metal oxides by chemical probe-assisted NMR for catalytic applications - Peng, Y (2017)
Semiconductive metal oxides are of great importance in environmental remediation and electronics because of their ability to generate charge carriers when excited with appropriate energy. The electronic structure, light absorption and charge transport properties have made the transition metal oxides an attractive material as photocatalyst. Recently, facet-engineering by morphology control has been intensively studied as an efficient approach to further enhance their photocatalytic performance. However, various processing steps and post-treatments used in the preparation of facet-engineered particles may generate different surface active sites which may affect their photocatalysis. Moreover, many traditional techniques (PL, EPR and XPS) used for materials characterization (oxygen vacancy, hydroxyl group, cation…etc.) are not truly surface specific but analyzing a range from surface few layers to bulk. Accordingly, they can only provide very limited information on chemical states of the surface active features and their distribution among facets, causing difficulties to unambiguously correlate facet-dependent results with activity. As a result, this often leads to different interpretations amongst researchers during the past decades. As the publications of titanium and zinc ranked top two among studies of first row of transition oxides in the past decades, this thesis will firstly review on the disagreements generated among researchers when they correlated the performance of ZnO and TiO2 with their facet activities based on traditional techniques. As there are shortcomings of these techniques in producing truly facet-dependent features, some results can be misleading and with no cross-literature comparison. To address these issues, we have developed a new technique "probe-molecule-assisted NMR" which allows a genuine differentiation of surface active sites from various facets. This surface-fingerprint technique has been demonstrated to provide both qualitative (chemical shift) and quantitative (peak intensity) information on the concentration and distribution of truly surface features among facets. In light of the new technique, this thesis will revisit the facet-dependent photocatalytic properties and shed light on these issues.